Complicity and Conspiracy - Туляков, В. О.; Туляков, Вячеслав Олексійович; Tuliakov, Viacheslav O. (My University, 2020)
The lecture of academic discipline "Criminal Law (General Part)" for students of National University "Odessa Law Academy".
video lecture
Tuliakov V. Complicity and Conspiracy : video lecture / V. Tuliakov. - Odessa, 2020. - Access mode: https://youtu.be/z_9y0IYQjuU
Keywords: criminal law; кримінальне право; уголовное право